Intelligent Transport Infrastructure Development, Leadership Governance, and Economic Growth: A Case Study on Ethiopia - BADADA Bayissa; RAMASWAMY Krishnaraj; GNANADHAS Delina (Communications of International Proceedings, 2024)
Ethiopia, a landlocked country in sub-Saharan Africa has given high priority to intelligent transport infrastructure. This study assesses the economic impact of intelligent transport infrastructure, and the moderating effect of leadership governance environments. To find the impact of intelligent transport infrastructure, the co-integration between intelligent transport infrastructure and economic growth is determined by performing F-test using the autoregressive distributed lag bound test model and then, the elasticity of economic growth is estimated using Ordinary Least Square estimation techniques. The results show that intelligent transport infrastructure has a signiﬁcant long-term positive impact on economic growth and the short-term dynamics shows the speed of adjustment is 10% adjusted each year toward the long-run path. The moderating eﬀect of the leadership governance environment examined using hierarchical multiple regression model yielded results about its substantial moderating eﬀect on the relationship between intelligent transport infrastructure and economic growth.
Keywords: intelligent transport Infrastructure; Economic Growth; Leadership Governance; GDP; Ethiopia